2003
DOI: 10.1038/sj.bmt.1704252
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and treatment of hemorrhagic cystitis in children given hematopoietic stem cell transplantation: a survey from the Italian association of pediatric hematology oncology–bone marrow transplantation group

Abstract: Summary:The purpose of this multicenter study was to assess the incidence and the treatment of hemorrhagic cystitis (HC) in 1218 pediatric patients, with a mean age of 10.8 years, who underwent hematopoietic stem cell transplantation (HSCT). In all, 44 patients (3.6%) developed HC a median 23 days after HSCT. The incidence of HC was higher in allogeneic than in autologous HSCT recipients (P ¼ 0.0001). Of the 44 patients, 37 (84%) recovered from HC in a median 30 days (range 3-100); the other seven children die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
80
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 45 publications
14
80
2
2
Order By: Relevance
“…Furthermore, two pediatric cohort studies reported an impact on mortality. 34,36 A single-center study has previously documented a longer median hospital stay for patient developing BKV-HC during the first 100 days after transplant (41 vs 26 days). 10 Our findings show that BKV-HC requires a median additional 10 days of hospitalization per patient, which represents 85% of the additional cost.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two pediatric cohort studies reported an impact on mortality. 34,36 A single-center study has previously documented a longer median hospital stay for patient developing BKV-HC during the first 100 days after transplant (41 vs 26 days). 10 Our findings show that BKV-HC requires a median additional 10 days of hospitalization per patient, which represents 85% of the additional cost.…”
Section: Discussionmentioning
confidence: 99%
“…18 In a single-center study on pediatric patients and in a retrospective study on adult and pediatric patients, the lack of recovery from HC has been associated with both a higher transplant-related mortality (72% vs 40%), and lower survival (43% vs 52%). 3,14 One issue still debated is the optimal dosage of CDV. Bernhoff et al…”
Section: Discussionmentioning
confidence: 99%
“…In allogeneic hematopoietic SCT (HSCT), hemorrhagic cystitis (HC) is a serious complication of the early post-engraftment period with a variable incidence from 3 to 70% [1][2][3] but in more recent reports it has occurred in 20-30% of patients. [4][5][6] Generally, HC is a painful complication that additionally prolongs the hospital stay for supportive measures, increases the need for blood transfusions, and, in the severe form, may obstruct the urinary tract.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine therapy for HC is based on intensive supportive treatment with hyperhydration, constant bladder irrigation, pain management and red cell or platelet transfusions. 2,13 Encouraging results with antiviral agents have been published; however, there is no evident proof in a large number of patients and mainly improve clinical symptoms. [14][15][16][17] The use of formalin, alum, prostaglandin E1, estrogens, FVIIa, factor XIII, hyperbaric oxygen treatment, intravesicular sodium hyaluronate, recombinant human epidermal growth factor or recombinant human GM-CSF has been described, but their efficacy remains controversial.…”
Section: Introductionmentioning
confidence: 99%